(untitled) (Journal of Information Technologies in Education (ITE), 2013)
The objectives of R&D management in NAPS of Ukraine are considered scientific activity as well as connected document types. There is the analysis of requirements for information systems to manage R&D, named “R&D”. Goals and objective, decisions design stages and prospects of “R&D" described. The developed model to build automatically tree folders and documents in R&D is explained. Current state of “R&D” implementation is shown.